MOWAT-WILSON SYNDROME: DEEP PHENOTYPING AND MOLECULAR CHARACTERISATION OF TWELVE NEW INDIVIDUALS - Umut Altunoğlu; Nilay Güneş; Gözde Tutku Turgut; Tuğba Kalaycı; Ayça Dilruba Aslanger; Murat Derbent; Serpil Eraslan; Birsen Karaman; Zehra Oya Uyguner; Beyhan Tüysüz; Yasemin Alanay; Hülya Kayserili Karabey (İstanbul Tıp Fakültesi Dergisi)
Objective: Mowat-Wilson syndrome (MOWS) is a rare multisystem malformation syndrome characterised by distinctive facial features, moderate to severe intellectual disability, and variable findings including callosal anomalies, ocular features, genital anomalies, congenital heart defects, and Hirschsprung’s disease. Pathogenic variants in the ZEB2 gene are implicated in the aetiology, with nearly all cases arising sporadically due to de novo variants. In addition to its low prevalence, the broad clinical spectrum observed among patients can make the diagnostic process challenging. This study aims to expand the clinical and molecular spectrum of MOWS by elucidating the characteristics of a new cohort. Material and Methods: Twelve patients with a clinical diagnosis of MOWS were included in the study. Following obtaining normal karyotype results, molecular analysis of ZEB2 was performed using Sanger sequencing.Results: Anthropometric measurements at birth and subsequent visits largely aligned with the national and MOWS growth charts, respectively. All patients exhibited moderate to severe intellectual disability and shared a characteristic facial gestalt. In addition to the well-described features, very rare or previously undescribed abnormalities comprising persistent left superior vena cava, choanal stenosis, shawl scrotum, and ocular anomalies were observed. Skin pigmentation defects were noted at significantly higher frequencies than those previously reported. Two patients displayed atypical features overlapping with CHARGE and Aicardi syndromes. We identified 12 heterozygous variants in ZEB2, five of which were novel. Conclusion: Deep phenotyping data of 12 patients enabled the identification of previously uncertain clinical associations and underrepresented features. The novel pathogenic variants identified here expand the molecular spectrum of ZEB2.